Sustainable Development and the Changes is the Modern Economic and Social Life (European Journal of Marketing and Economics, 2024)
In the contemporary world, with its high technologies, constantly developing and improving production processes and globalization, the issue of sustainable development is present in the agenda of the whole world. Moreover, the international business in all its variety of forms and operations, is an integral part of the economic life of each country. It contributes to the increase of the gross domestic product of developed countries and for the economic progress of developing countries. In this context, what becomes important is not only achieving economic growth, but also the ways it is achieved. That’s where the concept of sustainable development comes. The ideas of sustainable development, getting economic growth with care for the environment, reaching higher living standard while protecting the natural resources are extremely popular at the beginning of this century, when environmental disasters and economic crises caused by the scarcity of certain resources are a reality and are not limited to one specific country but affect the whole world. These problems inevitably lead to changes in the economic life, as it has to respond to the need of finding a new approach to achieve economic prosperity. Such changes in the economic and social life, for example, are the emergence of new economic sectors such as eco-manufacturing, bio-products, provision of environmental services, changes in some state policies such as initiating green procurement, green public-private partnership, green supply chains etc. This article is dedicated to revealing some of these changes which result from the current trend for sustainable economic development.
Keywords: sustainable development, international business, environment, green economy